Management of Blowout Fracture With Support of Video Endoscopy in a Pediatric Patient - Martins, Thiago Henrique; Bonardi, Joao Paulo [UNESP]; Vitti Stabile, Glaykon Alex; Dallazen, Eduardo; Hochuli-Vieira, Eduardo [UNESP]; Pereira-Stabile, Cecilia Luiz (Lippincott Williams & Wilkins, 2017)
Pure orbital fractures have the tendency to occur on medial wall and orbital floor; because these points are more fragile, the endoscopy can be utilized for accomplishing the task of repositioning the herniated content, as well as serving as an additional tool, helping to view the orbital defects through a transantral approach. The presented case is a female patient, 12 years old, who was diagnosed as having a pure blowout fracture, on right orbital floor, type trapdoor, with orbital content herniated toward the maxillary sinus. It was realized that a surgical procedure for reduction of orbital content through video endoscopy, via antral, allowed a great viewing of soft and hard structures, checking the positioning of implants and its relation with the orbital cavity, enabling installing through a small surgical access and minimum detachment, and favoring postoperative recovery.
Keywords: Endoscopy; orbital fractures; pediatrics